Factors associated with polypharmacy among the elderly in Dasmari?as, Cavite - Alvero, Rita Grace Y.
A survey was conducted in Dasmari?as, Cavite from September to December 1998 among 400 elderly citizens aged 65 years or more selected at random and interviewed to determine the prevalence of polypharmacy and to determine whether health status, social network and pharmacological concepts were associated with polypharmacy.The mean age of the respondents was 71 years with the oldest being 96. There were more women than men, with a sex ratio of 1.66:1 Majority of the respondents were married with 59having a surviving spouse. Twelve percent had no formal education, 71had some primary education and only 17of the respondents went beyond. Majority of the elderly lived with children and grand children (76) with only 4living alone. The average household size was 6 with a maximum of 14. Eighty-five percent of the respondents had a total household income less than P 10,000 per month. It was found out that 80of the elderly perceived themselves to be ill. A greater percentage, 82.5, sought formal consultation with healthgivers. Among those who sought consultation, majority consulted with physicians (90.0) followed a folk healers (4.8). The most common conditions were: hypertension (26), arthritis (12.3) and peptic ulcer disease (6.8). The average number of drugs taken by the elderly was 1.8 and the median was 2. The main sources of informal care were family members, particularly daughters, spouses and grandchildren. Majority of the elderly has no knowledge about side effects of drugs (97.8) and drug interactions (99.7). The information of the elderly about drugs came mainly from their doctors (87.1) and children (45.9).The prevalence of polypharmacy, defined as the intake of more medications than are indicated, was 37. The following were considered as significant factors of polypharmacy: perception of presence of illness, hospitalization within the past six months, consultation to a healthgiver, availability of family caregivers, knowledge of side effects and drug interaction and source of drug information.
Thesis (Master of Science in Epidemiology)-- University of the Philippines Manila.
Keywords: Aged -- Care; Aged -- Health and hygiene; Polypharmacy; Elderly